PERAMALAN TINGKAT PENGANGGURAN DI KOTA LAMONGAN MENGGUNAKAN METODE PEMULUSAN EKSPONENSIAL GANDA BROWN - Rosidah, Kamilatur; alfan, Aris; Isro'il, Ahmad (Universitas Negeri Surabaya, 2024)
Forecasting is a method in statistics that aims to estimate or predict a condition in the future. The results of forecasting can be used as a reference or indicator in predicting conditions at the next time. This research was carried out by predicting the unemployment rate in the city of Lamongan for the next period, using the Brown double exponential smoothing method based on data from 2001 to 2023. The forecasting accuracy method used in forecasting unemployment is Mean Absolute Percentage Error (MAPE) for calculate the percentage error for each ? parameter value. From the research results, the best ? parameter value was obtained for forecasting the unemployment rate in the city of Lamongan in the future by obtaining the smallest MAPE value chosen by trial and error.